2018
DOI: 10.1103/physrevmaterials.2.034404
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated spin one on a diamond lattice in NiRh2O4

Abstract: We report the discovery of a spin one diamond lattice in NiRh2O4. This spinel undergoes a cubic to tetragonal phase transition at T = 440 K that leaves all nearest neighbor interactions equivalent. In the tetragonal phase, magnetization measurements show a Ni 2+ effective moment of p eff = 3.3(1) and dominant antiferromagnetic interactions with ΘCW = -11.3(7) K. No phase transition to a longrange magnetically ordered state is observed by specific heat measurements down to T = 0.1 K. Inelastic neutron scatterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 64 publications
(78 reference statements)
3
42
0
Order By: Relevance
“…For the spin-1 system of interest in the context of NiRh 2 O 4 these findings support the notion that quantum fluctuations paired with strong geometric frustration can indeed prevent the formation of magnetic ordering and that the system remains fluctuating amongst different spin spiral states down to the zero temperature. However, when considering a slightly modified exchange model with two distinct types of next-nearest neighbor exchanges that has been proposed [19] for the tetragonal phase of NiRh 2 O 4 we find that this picture no longer holds. In fact, we find that the modified energetics strongly inhibit the spin spiral fluctuations and instead favor the formation of conventional Néel order for arbitrary spin length S. We will return to this point towards the end of the manuscript and discuss how to possibly consolidate these findings with the experimental absence of a thermal phase transition.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…For the spin-1 system of interest in the context of NiRh 2 O 4 these findings support the notion that quantum fluctuations paired with strong geometric frustration can indeed prevent the formation of magnetic ordering and that the system remains fluctuating amongst different spin spiral states down to the zero temperature. However, when considering a slightly modified exchange model with two distinct types of next-nearest neighbor exchanges that has been proposed [19] for the tetragonal phase of NiRh 2 O 4 we find that this picture no longer holds. In fact, we find that the modified energetics strongly inhibit the spin spiral fluctuations and instead favor the formation of conventional Néel order for arbitrary spin length S. We will return to this point towards the end of the manuscript and discuss how to possibly consolidate these findings with the experimental absence of a thermal phase transition.…”
mentioning
confidence: 82%
“…Such a description of the magnetism of A-site spinels in terms of classical local moments has proved sufficient to capture the physics of the Mn and Co-based spinels [11,[14][15][16] with local moments S=5/2 and S=3/2, respectively, while the physics of FeSc 2 S 4 (S=2) is dominated by the formation of a spin-orbit coupled local moment [17,18]. Earlier this year, the synthesis of the first spin-1 A-site spinel has been reported -NiRh 2 O 4 , which is found to exhibit no thermal ordering transition down to 0.1 K [19], possibly indicating the formation of a quantum spin liquid ground state. This motivates us to consider the quantum version of the minimal exchange model (1) for spins of arbitrary length S in this manuscript and ask whether qualitatively new physics arises in the crossover from the classical to the quantum regime (upon decreasing the spin length).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the counterpart insulating system, the frustrated local moment on the diamond lattice has been extensively studied as a spin liquid candidate [7][8][9]. A typical example is the magnetic spinel (AB 2 C 4 ) with the A site diamond lattice [10][11][12][13][14][15][16][17][18], where the properties of the disordered state are under intense debate. A (topological) Mott transition is expected to occur from a spin disordered phase to a Dirac semimetal phase by tuning the electron correlation [2,7].Organic molecular compounds have provided the platform for investigating the pressure-tuned Mott transition for the soft crystal.…”
mentioning
confidence: 99%
“…It was suggested that, the spin-one diamond lattice antiferromagnet with frustrated spin interactions may host a topological quantum paramagnet that is a spin analogue of topological insulator and protected by time reversal symmetry 29 . Quite recently, a diamond lattice antiferromagnet NiRh 2 O 4 with Ni 2+ spin-one local moments was proposed to fit into the early suggestion 30 . NiRh 2 O 4 is a tetragonal spinel and experiences a structural phase transition from cubic to tetragonal at T = 380K 30,32,33 .…”
mentioning
confidence: 90%